Distal Bone Lesions Diagnosed by Radiographic Examination in Dairy Cows without Claudication - Barbosa, Antônio Amaral; Luz, Gabriela Bueno; Torres, Aníbal Janczak; Rabassa, Viviane; Ulguim, Rafael; Del Pino, Franciso; Correa, Marcio Nunes; Martins, Charles Ferreira (Acta Scientiae Veterinariae, 2018)
Background: During decades, dairy cows have been selected for its productive character, with the main focus on the breeding production, being submitted to constant conditions of metabolic disorders, likewise submitted to permanent or intermittent episodes of systemic and / or mechanical aggression, anatomofunctional of its orthopedic system, appearing locomotion injuries. The present approach brings up the variable aspect of lesions in the extensor process of the third phalanx bone, diagnosed by digital radiography, in 17 Holstein cows, with or without joint involvement, the study was conducted in a commercial farm located in the South of Rio Grande do Sul State, Brazil. Case: This case report describes the identification and the appearance of lesions on the extensor process of the third phalanx bone in dairy cattle from a commercial herd. 17 Holstein cows with three lactations, with average production in two milking of 30.67 ± 5.39 L of milk submitted to semi-extensive system, with daily walk of 2.2 km between pasture, food and milking parlor. Weekly, the cows were submitted to clinical diagnosis and radiological exploration, on two periods (pre- and postpartum), from 14 days prepartum to 50 days postpartum. All animals despite the zero score of locomotion, demonstrated no abnormalities of posture or walking, however expressed at least one radiographic change in at least one member. Thereafter, radiographic lesions were evaluated for their variety and severity, indeed animals that had only injury extensor process, with fracture and / or joint involvement were detected. In the animals evaluated in this study there was antecedent clinical record of macroscopic lesions to the digit, without lameness. Clinically, the cows manifested macroscopic signs and according to the foot condition frequency was observed: white line extension (23.72%), scissor claw (22.03%), horizontal lines (18.64%), dual sole (13.6%), wall bleeding (8.47%), crack in the wall (6.77%), corkscrew claw (5.08%) and a lower frequency of clef white line (1.69%), and the presence of lameness was not observed. Among the radiographic lesions in thoracic digits, it was found the following array, according with the frequency distribution: proliferative bone reaction in the region of the extensor process in 73.5% (nnails=34) of forelimbs from the animals, distal interphalangeal osteoarthritis (13.7%) and extensor process fracture was observed only in 2% of the digits. Discussion: In the animals evaluated in this report, there was clinical record of macroscopic lesions antecedent of aggression to the digit, without lameness, even with these bone lesions detected by digital radiographic examination, in other words, chronic lesions in the extensor process, with or without joint involvement, did not promote nociceptive signals in the locomotion of the cows, further emphasizing the importance of digital imaging in the detection of relevant subtle lesions that may subsequently lead to serious failings by the involvement of the distal interphalangeal joint. The technology of digital radiology provides a higher accuracy of diagnosis of lesions on the locomotor system, nevertheless, in dairy cattle, its use is still limited when compared to horses. Up to now, there are few studies that report the occurrence of lesions in the extensor process of the third phalanx in cattle. Extensor process lesions may be more common in dairy herds, given the absence of complementary diagnostics.